Eight weeks of sofosbuvir/velpatasvir for genotype 3 hepatitis C in previously untreated patients with significant (F2/3) fibrosis. Issue 4 (13th December 2019) - Boyle, Alison; Marra, Fiona; Peters, Erica; Datta, Shouren; Ritchie, Trina; Priest, Matthew; Heydtmann, Mathis; Barclay, Stephen T.
Summary: Twelve weeks sofosbuvir/velpatasvir (SOF/VEL) is a highly effective pan‐genotypic regimen for hepatitis C. Phase 2 data suggest 8 weeks of treatment may be sufficient for previously untreated noncirrhotic patients with genotype 3 (GT3) infection. To maximize the number of patients potentially cured within a fixed treatment budget, we elected to treat such patients locally eligible for treatment (F2/3), with 8 weeks of SOF/VEL. By local protocol, treatment‐naive patients with F2 (LSM > 6.9kPa < 9.5kPa) or F3 fibrosis (≥9.5kPa < 12.5kPa) were eligible for 8‐week SOF/VEL treatment. Patients commencing treatment before 1 Oct 2017 were identified from the Scottish HCV database. Baseline and treatment outcome data obtained. Ninety patients were included for analysis (72 (80%) male, mean age 45 (IQR ± 8.4), 28 (31.1%) F3 fibrosis). Opioid agonist therapy (OAT) was prescribed in 82 (91.1%) patients. Of 49 patients attending Glasgow city Alcohol and Drug Services, 27 (55.1%) had evidence of recent drug use (< 3 months) including 8 (16.3%) with self‐reported intravenous drug use. On an intention‐to‐treat basis, SVR rates were 86/90 (95.6%, 95% CI 89.0‐98.8). Excluding those who prematurely discontinued treatment (n = 4), died prior to SVR testing (n = 1) or whom experienced reinfection (n = 1), per‐protocol SVR rate was 84/84 (100%, 95% CI 95.7‐100.0). In conclusion, eight‐week SOF/VEL is highly effective in treatment‐naive GT3 patients with significant fibrosis. This offers a non‐protease inhibitor‐based 8‐week regimen which may be useful for complex drug interactions or where time‐limited opportunity for treatment. In limited resource settings, reduction in drug acquisition costs may help achieve progress towards the goal of HCV elimination.